Analisis Reskilling Kompetensi Finansial Manajerial UMKM di Era Transformasi Digital - I Dewa Nyoman Arta Jiwa; Gede Arnawa; I Nyoman Suandana; Ni Putu Sri Wati (Widya Amerta, 2026)
MSMEs are important business activities that are able to help improve a country's economy through gross domestic product (GDP) produced. Its growth will be a priority and the government's commitment to improve the economy. Digital transformation requires MSMEs to carry out reskilling managerial competence to improve competitiveness and business sustainability. However, the gap between employee, manager, owner skills and will is a major challenge in the process.The challenge of MSME managerial competency in the era of digital transformation is employee resistance to changes in skills improvement (reskilling) which is greatly influenced by several factors such as the income and education levels of MSME employees and managers.The results of the study indicate that partially there is a positive and significant influence of the income level variable on managerial financial variables. There is a positive and significant influence of the education level variable on managerial financial variables of MSMEs in Singaraja, Buleleng Regency. Simultaneously, it shows that the income level and education level variables have a positive and significant influence on managerial financial variables. The income level variable is the variable with a higher positive influence and significance on managerial financial variables of MSMEs in Singaraja, Buleleng Regency, compared to the education level variable.